Low-energy Selective Laser Trabeculoplasty Repeated Annually: Rationale for the COAST Trial. Issue 7 (7th July 2021) - Realini, Tony; Gazzard, Gus; Latina, Mark; Kass, Michael
Abstract : The recent Laser in Glaucoma and Ocular Hypertension Trial provided the evidentiary basis for a paradigm shift away from the historical medication-first approach to glaucoma--which has numerous limitations, the most important of which is poor adherence to therapy --and toward a laser-first approach. Now 20 years after its commercialization, selective laser trabeculoplasty (SLT) is routinely performed consistently with its initial description, with energy titrated to the appearance of fine, champagne-like cavitation bubbles. A recent data set suggested that lower energy SLT, applied as primary therapy and repeated annually irrespective of intraocular pressure--rather than pro re nata when its effect wanes and irrespective of intraocular pressure rises --yields longer medication-free survival than standard energy SLT repeated pro re nata. A new study--Clarifying the Optimal Application of SLT Therapy --has been initiated to explore this preliminary finding in a pair of consecutive randomized trials. Herein, we provide an evidence-based rationale for the use of low-energy SLT repeated annually as primary therapy for mild to moderate primary open-angle glaucoma or high-risk ocular hypertension.